Control IMC de la presión de los pozos de petróleo durante la perforación modelado como un proceso integrativo con tiempo de retraso (2021)
Controlling the pressure of oil wells during drilling can be one of the most complex and dangerous processes operating stage. This study proposes the design of an internal model controller (IMC) to control the pressure at the bottom of wells during drilling operations based Manage Pressure Drilling (MPD). MPD adds a control valve in the drilling system to have another manipulate variable on the well pressure. In the first part of this work, there was obtained a mathematical model of the process, which is founded on fluid mechanics (state equation, the Reynolds transport equation: continuity and momentum). The dynamic process presents an integrating element, which makes the process dynamics difficult to handle because any disturbance may alter its stability. Still it becomes more complex in the presence of a delay time in the system model. In the second part, was designed an IMC controller for controlling the integrative process with the addition of time delay looking for the best stability and robustness of the process. Finally, the proposed controller is performed by simulations that show its feasibility in the presence of common problems during drilling, which were tested as disturbances in closed loop system (loss circulation fluid, influxes, pipe addition and loss of pump power). The performance of the process in closed loop is compared with a classical PI.